Priva : shaping sustainable cities - Boyaninska, Daniela, (SAGE Business cases., 2020)
In 2020 Priva was a leading global high-tech company that provided equipment, software and management strategies for climate control, energy savings and the optimal re-use of water in horticulture, building automation and indoor farming. It was a second-generation family business whose CEO, Meiny Prins, rebranded Priva to highlight innovation and sustainability, in addition to expanding Priva’s business ventures and partnerships around the world. Given its expertise and experience, Priva was well situated to use its technological solutions to assist densely populated world regions in tackling their energy, food and water issues. It did so via its ‘Sustainable Urban Delta’ initiative, which became Priva’s area of focus.